2013
DOI: 10.1089/ham.2012.1111
|View full text |Cite
|
Sign up to set email alerts
|

Dead Space Mask Eliminates Central Apnea at Altitude

Abstract: Travelers to high altitude may have disturbed sleep due to periodic breathing with frequent central apneas. We tested whether a mask with added dead space could reduce the central apneas of altitude. 16 subjects were recruited, age 18-35, residing at 4600 ft (1400 m). They each slept one night with full polysomnographic monitoring, including end tidal CO2, in a normobaric hypoxia tent simulating 12,000 ft. (3658 m) altitude. Those who had a central apnea index (CAI) >20/h returned for a night in the tent for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The increase in sleep-disordered breathing observed in HH compared to NH is, however, more difficult to explain. The possible increase in physiological dead space in HH is probably not the only cause because previous studies by our group and others showed that an increase in dead space (using a face mask) could significantly decrease altitude-induced central respiratory events 43,44 (even though this experimental increase in dead space was probably much larger). Altered environmental conditions (comfort, temperature) at high altitude compared with simulated altitude could play a role but the arousal index was not different between both conditions.…”
Section: Discussionmentioning
confidence: 84%
“…The increase in sleep-disordered breathing observed in HH compared to NH is, however, more difficult to explain. The possible increase in physiological dead space in HH is probably not the only cause because previous studies by our group and others showed that an increase in dead space (using a face mask) could significantly decrease altitude-induced central respiratory events 43,44 (even though this experimental increase in dead space was probably much larger). Altered environmental conditions (comfort, temperature) at high altitude compared with simulated altitude could play a role but the arousal index was not different between both conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Nasal EPAP is also more logistically feasible for prevention of nocturnal hypoxia than dead space masks, which have shown to decrease central apnea but not AMS (Patz et al, 2013). The challenge of implementation of the studied device was the level of user discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal administration of supplemental O 2 sufficient to return SaO 2 within 2 to 3% of sea level values eliminated periodic breathing at high altitudes almost immediately 4, 77 . Oral acetazolamide elicits steady-state hyperventilation and reduces PaCO 2 and loop gain, thereby reducing periodic breathing, in sleeping sojourners, whereas adding 1 to 2 mm Hg PaCO 2 —via increased fractional inspired carbon dioxide (FiCO 2 )—is sufficient to completely eliminate periodic breathing via reduced plant gain 3, 4 . OSA patients sojourning at even moderate altitudes experience periodic CSA and adding oral acetazolamide to their CPAP treatment significantly reduced both central and obstructive apneas 57 .…”
Section: Non-positive Airway Pressure Treatments Of Central Sleep Apnmentioning
confidence: 99%
“…The periodic waxing and waning of tidal volume (Vt) followed by apneas of at least 10 seconds’ duration accompanied by intermittent hypoxemia and transient cortical electroencephalography arousal are typical of non-rapid eye movement (NREM) sleep in congestive heart failure (CHF) with periodic cycles of at least 50 seconds. CSA and “cluster type” periodic breathing with short periodic cycles (10–25 seconds) are common in healthy sojourners during NREM sleep at high altitudes (>3000 m, oxygen saturation [SaO 2 ] of about 90%) and even at more moderate high altitudes in susceptible people, especially with prolonged residencies 3, 4 . This cluster-type periodic breathing with relatively short cycles is also common at sea level in over half of chronic opioid users, and the severity of CSA is proportional to opiate dose 5 .…”
Section: Introductionmentioning
confidence: 99%